Effect of Fortified Daqu on the Microbial Community and Flavor in Chinese Strong-Flavor Liquor Brewing Process - He, Guiqiang; Huang, Jun; Zhou, Rongqing; Wu, Chongde; Jin, Yao (Frontiers in Microbiology, 2019)
Daqu, an important fermentation starter for the production of Chinese liquor, as used in the current study included traditional Daqu and fortified Daqu inoculated with Bacillus velezensis and Bacillus subtilis. To evaluate the effect of fortified Daqu on strong-flavor liquor production, the differences of microbial communities among three inoculation patterns of fermented grains (FG) were analyzed by the Illumina MiSeq platform. A higher relative abundance of dominant genera including Bacillus, Lactococcus, Aspergillus, and Candida, and lower relative abundance of Lactobacillus, were observed in FG50, in which mixed Daqu (traditional: fortified Daqu = 1: 1, w/w, 50% fortified Daqu) was used as the starter. Then, volatile compounds of their distillations were also examined by HS-SPME-GC-MS. The results showed that the contents of skeleton flavor components, mainly including important esters and aromatic compounds, were higher in the corresponding liquor L50, which distillated from FG50. Moreover, most esters mainly positively correlated with Lactobacillus and Candida in the bottom layer of FG fermented with 50% fortified Daqu (FG50-B). Aromatic compounds were strongly positively correlated with Bacillus and Aspergillus in the middle layer of FG with 50% fortified Daqu used (FG50-M). In particular, hexyl hexanoate showed a positive correlation with higher abundances of Ruminococcus in the FG with addition of 100% fortified Daqu (FG100). This study observed microbial compositions in the FG with fortified Daqu addition, and it further revealed the correlations between pivotal microbes and main flavor compounds. These results may help to develop effective strategies to regulate microbes for the brewing process and further improve the flavors of Chinese liquor.